ANALISIS SEMIOTIKA MAKNA TOXIC RELATIONSHIP DALAM SERIAL DRAMA “YANG HILANG DALAM CINTA” - Kurniawan, Yoseph Wahyu (Universitas Bunda Mulia, 2024)
Toxic relationship is a social issue that can occur in the real life, especially in an interpersonal relationship. This can be emphasized through the numbers of violence against couples in Indonesia which continues to increase from year to year. The issue of toxic relationship then tried to be raised through one of the drama series, namely